Health as a social representation: The phenomenon of health within the daily life of nicaraguan migrants in Costa Rica - Mora-Rivera, Wendel (Población y Salud en Mesoamérica, 2021)
Introduction: Health is loaded with symbolisms and practical manifestations that differ according to social groups and sociocultural contexts. In order to make everyday life and needs visible, the Theoretical Paradigm of Social Representations provides the theoretical-methodological bases necessary to understand the common sense knowledge associated with health among the Nicaraguan migrant population in Costa Rica. Methodology: Qualitative study with ethnographic approach that aimed to identify the social representation of health, through the process of objectification, present among Nicaraguan migrants living in Costa Rica. Data collected through semi-structured interviews, participant observation, and field diaries. Processing according to Content Analysis. Results: The social representation of health found behaves analogously to a formula; where, the search for peaceful environments is added to the achievement of financial stability to result in two interdependent representations: 1) Health as physical-mental strength; and 2) Health as a future and abstract sensation of well-being, happiness and transcendence. The socio-political antecedents in Nicaragua, the migratory process, and the adaptation to Costa Rica play a preponderant role in shaping the representation on health. Conclusion: Social representations about health have direct practical implications on the ways of life and needs of migrant groups. Understanding their common sense knowledge allows to move towards more contextualized public policies. More integration of the thoughts, opinions and feelings of migrants in decision-making platforms is recommended.